Effect of stage of glycerolization on viability and acrosomal integrity of buffalo spermatozoa during cryopreservation - SINGH, PAWAN; SINGH, SAJJAN; SINGH, INDERJEET (The Indian Journal of Animal Reproduction, 2023)
This study was planned in order to evaluate the effects, if any, of the stage of glycerol addition on survival and acrosomal integrity of buffalo sperm cells undergoing cryopreservation. Two equal parts oftris-yolk extender were prepared, part I without and part 2 with 12.8% glycerol. Fifteen ejaculates, obtained from five breeding buffalo bulls using artificial vagina, were half diluted with part-I extender immediately after collection. This half-diluted semen was then divided into two aliquots, to which part-2 extender (with glycerol) was added either at room temperature (Group I) or after cooling to 5°C (Group 2) to give final glycerol concentration of 6.4%. The proportion of spermatozoa exhibiting forward and backward motility, live sperm count and percentages of spermatozoa with intact acrosome, were recorded. Significantly higher percentages of spermatozoa were recorded moving backwards, before freezing and post-thaw, when glycerol was added at 5°C, as compared to at room temperature, but no significant effect of stage of glycerolization was found on live sperm count and acrosomal integrity. It is concluded that addition of glycerol to buffalo semen either at room temperature or at 5°C during cryopreservation does not affect sperm survival rate and acrosomal integrity, in spite of altering the motility pattern of spermatozoa.